Pengaruh Company Size, Proporsi Komisaris Independen Dan Thin Capitalization Terhadap Tax Aggressive - Ananda Reneisha Putri Wibowo; Muhammad Ridwan (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
This study aims to analyze and test the influence of Company Size, the Proportion of Independent Commissioners, and Thin Capitalization on Tax Aggressiveness. This study uses a quantitative approach, using secondary data obtained from the financial reports of energy sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023. The sampling technique used purposive sampling, resulting in 16 companies meeting the criteria, with a total of 80 observations over five years. Data analysis was conducted using descriptive statistics, panel data regression model selection, and hypothesis testing using EViews 12 software. The results indicate that simultaneously, the variables Company Size (X1), the Proportion of Independent Commissioners (X2), and Thin Capitalization (X3) significantly influence Tax Aggressiveness (Y). However, partially, only the Proportion of Independent Commissioners (X2) and Thin Capitalization (X3) significantly influence Tax Aggressiveness, while Company Size (X1) has no significant effect. The results of the coefficient of determination test indicate an adjusted R-squared value of 0.1671, or 16.71%. This means that the three independent variables in this study are able to explain 16.71% of the dependent variable, Tax Aggressiveness. Meanwhile, the remaining 83.29% is explained by other variables outside this research model.